2014
DOI: 10.1063/1.4886119
|View full text |Cite
|
Sign up to set email alerts
|

GeTe sequences in superlattice phase change memories and their electrical characteristics

Abstract: We studied GeTe structures in superlattice phase change memories (superlattice PCMs) with a [GeTe/Sb2Te3] stacked structure by X-ray diffraction (XRD) analysis. We examined the electrical characteristics of superlattice PCMs with films deposited at different temperatures. It was found that XRD spectra differed between the films deposited at 200 °C and 240 °C; the differences corresponded to the differences in the GeTe sequences in the films. We applied first-principles calculations to calculate the total energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 14 publications
4
50
2
2
Order By: Relevance
“…In that connection, chalcogenide superlattices (CSL) [123,124] and nanocrystals [125,126] were investigated for their capabilities to serve in such systems. In particular, interfacial phase-change materials (iPCMs) [127][128][129], in which the transformations do not occur between an amorphous and a crystalline phase, but between two crystalline phases, are of great interest as candidate systems. The more recent determinations of the crystal structure for the ternary Ge 4 Se 3 Te [31] (Figure 7) indicated that the type of structure observed for that chalcogenide may serve as an archetype for future PCMs.…”
Section: The Role Of Vacancies and Structural Preferences In Phase-chmentioning
confidence: 99%
“…In that connection, chalcogenide superlattices (CSL) [123,124] and nanocrystals [125,126] were investigated for their capabilities to serve in such systems. In particular, interfacial phase-change materials (iPCMs) [127][128][129], in which the transformations do not occur between an amorphous and a crystalline phase, but between two crystalline phases, are of great interest as candidate systems. The more recent determinations of the crystal structure for the ternary Ge 4 Se 3 Te [31] (Figure 7) indicated that the type of structure observed for that chalcogenide may serve as an archetype for future PCMs.…”
Section: The Role Of Vacancies and Structural Preferences In Phase-chmentioning
confidence: 99%
“…The TEM views showed that the [GeTe = 1 nm/ Sb 2 Te 3 =1 nm] periodic unit had a rough surface but that the [GeTe = 1 nm/ Sb 2 Te 3 = 4 nm] one was uniform. The results of synchrotron radiation Xray diffraction (XRD) measurements suggested that the crystal structure of the GeTe films in the [GeTe = 1 nm/ Sb 2 Te 3 = 4 nm] periodic unit was not cubic but rather was aligned to the caxis of the hexagonal Sb 2 Te 3 layer [9].…”
Section: A Physical Vapor Depositionmentioning
confidence: 99%
“…The superlattice structure is designed such that the change in the Ge-Te bonding state does not require an amorphouscrystalline phase transition. Figure 1(b) shows the atomic structure of the GeTe=Sb 2 Te 3 superlattice [20][21][22] given by Tominaga and coworkers. Each of the Ferro, Petrov, and Inverted Petrov structures consists of nine atomic layers of -Te-Sb-Te-Te-Ge-Te-Ge-Te-Sb-, -Te-Sb-Te-Ge-TeTe-Ge-Te-Sb-, and -Te-Sb-Te-Te-Ge-Ge-Te-Te-Sb-, respectively.…”
Section: )mentioning
confidence: 99%
“…That is, the atomic structures of the HRS and LRS remain unclear and the resistive switching mechanism has yet to be clarified. 22,23,[26][27][28][29][30][31] In this study, we propose a mechanism for unipolar resistive switching and describe the new LRS and HRS structures based on the results of first-principles molecular dynamics (MD) simulation. Basically, unipolar switching is current-driven.…”
Section: )mentioning
confidence: 99%